Theory of Constructed Emotion: Emotional vocabulary and emotional intelligence - Calero, Alejandra Daniela (2023)
The present work aims to study the relationship between perceived emotional intelligence, and general and emotional vocabulary. Undergraduate Psychology (N = 99) and Design (N = 44) students completed a number of tests about emotional intelligence (TMMS-21), general vocabulary (BAIRES-A), and emotional vocabulary respectively. The predictive effect of emotional vocabulary differed across different factors of emotional intelligence (positive in attention to feelings and negative in emotion repair), while a positive association was found in psychology students with more years completed at university. Psychology students had higher emotional vocabulary than Design students. Emotional vocabulary had limited influence on emotional intelligence, contrary to the theory of Constructed Emotion.